Long ride home - L'Amour, Louis (New York Bantam Books, 1989)
No one brings to life the Old West like Louis L'Amour Collected here for the first time, these vintage frontier stories introduce you to lawmen and loners, ranchers and renegades, gunslingers, cardsharps, bank robbers, etc In these pages L'Amour brings to life such classic characters as the Cactus Kid, Tensleep Mooney, One-Eared Tim, and the gunfighter Kim Sartain. These are frontier tales as only L'Amour can tell them--stories that surprise like the sharp crack of a Winchester and move like the lonely howl of the wind across an empty plain on the long ride home.
89721
Keywords: Short stories; Western stories